Screening of factors influencing the yield of Citrus hystrix leaves essential oil extracted via pressurized hot water extraction based on resolution V fractional factorial design - Abdul Halim, Noor Amirah; Zainal Abidin, Zurina; Siajam, Shamsul Izhar; Chong, Gun Hean; Harun, Mohd Razif (Wiley, 2020)
Pressurized hot water extraction (PHWE) could be a better alternative in enhancing the yield of valuable Citrus hystrix leaves essential oil. Thus, the fractional factorial design based on resolution V was used to assess the crucial factors that affect the essential oil yield (%Y) extracted from Citrus hystrix leaves through a PHWE. A maximum Y% of 1.63% was successfully isolated at conditions involving 0.08% moisture content, 1 mm particle size, 1:0.2 ml/g solvent-to-sample ratio, 30 min extraction time, and 120°C extraction temperature. Moisture content and particle size were the main effects that significantly affect the %Y, while the extraction time and solvent-to-sample ratio exhibited a moderate effect on %Y, followed by extraction temperature that showed the least effect on %Y. A developed regression model has shown good correlation and adequacy on %Y. Based on the compositional analysis, neoisopulegol hydrate appears to be the main constituents of the oil obtained.